2023
DOI: 10.3390/healthcare11071029
|View full text |Cite
|
Sign up to set email alerts
|

The Masticatory Structure and Function in Children with Cerebral Palsy—A Pilot Study

Abstract: (1) Background: Muscle tension around the head and neck influences orofacial functions. The data exist concerning head posture during increased salivation; however, little is known about muscle tightness during this process. This study aims to investigate whether or not any muscles are related to problems with eating, such as drooling in individuals with cerebral palsy; (2) Methods: Nineteen patients between the ages of 1 and 14 were examined prior to the physiotherapy intervention. This intervention lasted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Studies have shown that therapy based on the Bobath concept improves gross motor function [ 16 ], postural balance [ 36 , 37 , 38 ], and coordination, in terms of feeding and swallowing activity [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that therapy based on the Bobath concept improves gross motor function [ 16 ], postural balance [ 36 , 37 , 38 ], and coordination, in terms of feeding and swallowing activity [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kangalgil, on the other hand, stated that behaviors such as keeping food in the mouth, choking while feeding, and food refusal are factors that cause feeding problems in children with CP aged 7-17 [12]. Although studies have shown that motor, swallowing, and chewing issues are the most common causes of feeding problems [4,13,14], research has also shown that sensory processing impairments can induce feeding problems related to the manipulation of solid foods in the mouth [15]. It has been reported that eating problems due to sensory reasons may result in oral intolerance, primarily due to the flavor, texture, and hardness of the meal, and that this circumstance also prolongs feeding times [16].…”
Section: Introductionmentioning
confidence: 99%